Systematic Review of Learning Method for Teaching Arabic Listening and Speaking Skills - Sri Wahyuni; Mahyudin Ritonga; Windy Afrianti (Al-Hayat: Journal of Islamic Education, 2023)
This research discusses appropriate learning methods for learning Arabic listening and speaking skills. The study's importance is based on learners' weak listening and Arabic speaking skills in Indonesia. The research was conducted with a qualitative approach, and data was collected from books, journals and experts' thoughts related to the research theme. The data was obtained with the help of publish or perish, which was then mapped with Vosviewer. After that, the data were analyzed using comparative techniques. Based on the literature, listening skills are the first means for humans to interact with each other. In istima' activities, a person will recognize vocabulary (mufradat), sentence components, and sentence structure. Learning by listening can be performed by listening to conversations, short stories, verbal questions, and chain messages. Speaking skills are related to the ability to articulate words to convey information through ideas, responses, or feelings. Speaking skills can be learned from the beginner and intermediate levels to the highest levels. All of these levels have the same method except for material difficulties. The novelty of this research is the position of the researcher's thoughts among various opinions of academics, namely the elaboration of ideas that are by the context of learning Arabic listening and speaking skills for students in Indonesia. The researcher rejects some opinions and strengthens other views, so the position of the results of this research is in the form of elaboration.